Strategi dalam Meningkatkan Pembakuan Bahasa Indonesia Bagi Mahasiswa Teknik Informatika di Universitas Widya Darma Klaten - Mira Erlinawati; Tiyan Ganang Wicaksono (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2020)
The purpose of this study is to describe strategies to improve the standardization of the language used by Informatics Engineering students at Widya Darma Klaten University. The type of research used is a qualitative approach to qualitative methods. Data collection techniques, namely oral collected by observation method, structured interviews, questionnaires and literature study. The subjects in this study were language standardization. The object of research is the elements which together with the research objective form the data and the data context. The object in this research is the implementation of computer terms applied by students. As for how to analyze using data reduction, data presentation and drawing conclusions. The existence of language can make it easier when we communicate. Language can also be used as an intermediary in a society and interaction individually or socially. Strategy is the science or art of using all the nation's resources to carry out certain policies in war and peace. Which can be considered directly related to careful language teaching and to activities to achieve specific goals. Indonesian uses certain terms to express certain things or fields. A term is a word or phrase that is used as a name or symbol and which carefully expresses the meaning of a concept, process, state or characteristic that is unique in the fields of science, technology and the arts. The combination of advances in computer technology and communication technology has produced new vocabulary / terms in that field. Language standardization must be applied and must be implemented in learning during lectures. Keywords: Language Standardization, Strategy.